Dermatofibrosarcoma protuberans. - FRANCO-RIVERA, CLAUDIA; PRISCILLA HERNÁNDEZ-ORTEGA, ANA; ANTONIO HIDALGO-OCHOA, MIGUEL; ULISES ALAS-PINEDA, CÉSAR; ROBERTO ALVARADO-GUEVARA, CARLOS (Acta Medica Colombiana)
Introduction: dermatofibrosarcoma protuberans (DFSP) is a rare superficial sarcoma arising from dermal fibroblasts, that affects the dermis and subcutaneous tissue, with the potential for muscle and bone invasion, and is locally aggressive. We present a case of DFSP in a young patient, highlighting the importance of appropriate diagnosis and treatment. Clinical case: an 18-year-old male, with no history of toxic ingestion or chronic diseases developed an asymptomatic lesion in the right scapular area over three months. It began as an indurated plaque which grew, with the subsequent appearance of a nodular lesion. An incisional biopsy was done, along with histopathological and immunohistochemical studies, confirming the diagnosis of DFSP. A computed tomography scan was done to rule out metastasis, as well as a molecular study. The physical exam showed an oval 3 x 4 cm plaque with a 2 x 2 cm central nodule. The biopsy confirmed intermediategrade DFSP. The immunohistochemical studies were positive for CD34, C163, FXIII-a and 5% Ki67. The tomography showed no metastasis. The molecular study did not show the disease’s characteristic translocation. A wide excision of the tumor was done with Z-flap reconstruction. The surgical site healed properly with no recurrence. Discussion: DFSP, while rare and frequently misdiagnosed, should be considered when slow-growing skin lesions are encountered. The main treatment is wide surgical excision, due to its infiltrative nature. The case we have presented shows the importance of appropriate diagnosis and treatment to avoid recurrence and preserve the functionality of the affected area.